Natural History of Ventriculomegaly in Fetal Agenesis of the Corpus Callosum. (9th September 2019) - Masmejan, Sophie; Blaser, Susan; Keunen, Johannes; Seaward, Gareth; Windrim, Rory; Kelly, Edmond; Ryan, Greg; Baud, David; Van Mieghem, Tim
Abstract : Objectives: To assess the natural evolution of the size of the fetal lateral ventricles throughout pregnancy in fetuses with callosal anomalies. Methods: Cases of fetal callosal anomalies were retrospectively classified as isolated or complex based on the presence of other structural or genetic anomalies. Longitudinal ultrasound studies were reviewed, and postnatal outcomes were retrieved for isolated cases. Results: In 135 fetuses, those who first presented after 24 weeks' gestation were more likely to have ventriculomegaly (n = 58 of 68 [85%]) than those who presented before 24 weeks (n = 39 of 67 [58%]; P  < .001). In 79 cases that had longitudinal follow‐up, the mean increase in ventricular width was 0.6 mm/wk, without a significant difference between isolated and complex cases (mean ± SD, 0.6 ± 1.5 versus 0.6 ± 1.1 mm; P = .45). Conclusions: Callosal anomalies are associated with progressive ventriculomegaly on prenatal ultrasound imaging, without a difference between isolated and complex anomalies. This feature should be considered part of the disease spectrum. The consequence of progressive ventriculomegaly on the long‐term neurodevelopmental outcome is still unknown, and further studies should be aimed at obtaining long‐term follow‐up of these cases.